Programming the finite element method - Smith, I. M. 1940-; Griffiths, D. V.; Margetts, Lee (Wiley, 2014)
"Provides an updated version of Fortran 2003 (all the Fortran programs and subroutines are listed in full in the text but will also be made available online)"--